Evaluation of the Influence of Thermal Comfort (PMV) of Classrooms on Teachers' Work Stress Levels in Dry Tropical Areas (Study at SDK Maumere II, Sikka Regency) - Da Mendez, Martina Rudolfa; Tandafatu, Maria Carolina (Cebong Journal, 2024)
This study aims to analyze the effect of thermal comfort (PMV) in classrooms on the level of work stress of teachers in dry tropical areas, especially in SDK Maumere II, Sikka Regency. Quantitative research methods were used by involving all teachers as samples. Data collection was carried out by measuring the physical condition of the classroom and distributing questionnaires. The results showed that the thermal conditions in the classroom did not meet comfort standards, with PMV values ​​​​outside the comfort range. Correlation and regression analysis showed a significant relationship between thermal comfort and the level of work stress of teachers. The higher the level of thermal comfort, the lower the level of work stress experienced by teachers. The results of this study concluded that thermal comfort is an important factor that affects the level of work stress of teachers and needs to be considered in efforts to improve the quality of the work environment in schools